Development of Patin Fish Cooking Skills at SMAK Kalam Kudus Sukoharjo - Savira Rizki Pradiati; Zahra Vira Firliyanda; Abang Ilman Qaultsabit (LPPM UIKA Bogor, 2023)
SMA Kristen Kalam Kudus optimizes its collaboration with universities to improve activities, programs, and the school curriculum related to developing the knowledge and skills of its students. The Master Chef television show has inspired SMAK Kalam Kudus students to have a career in the food industry. Therefore, to develop student's skills in the culinary field, the community outreach team conducted training on processing Patin catfish along with various sauces for students at SMAK Kalam Kudus. Patin catfish was chosen because the product is easy to obtain, the price is affordable, and it has high nutrition. The community outreach activity was carried out at SMAK Kalam Kudus, Sukoharjo Solo, and was attended by 130 students in grade 11. The process of implementing the activity, from preparation to completion, was carried out over 2 months, from 7 August to 7 October 2022, while the direct activity was carried out on October 6, 2022. The activity stages consist of preparation, material provision, cooking demonstration, and evaluation. After the activity was completed, participants gained knowledge and skills in cooking processed catfish with a variety of sauces, motivation to take part in cooking training activities, and were satisfied with the progress of the training activities.